Metal Bromide Controlled Interfacial Aromatization Reaction for Shape‐Selective Synthesis of Palladium Nanostructures with Efficient Catalytic Performances. Issue 29 (13th June 2016) - Dutta, Soumen; Ray, Chaiti; Roy, Anindita; Sahoo, Ramkrishna; Pal, Tarasankar
Abstract: Herein, the effect of diverse metal bromides for the shape evolution of palladium nanostructures (Pd NS) has been demonstrated. Aromaticity‐driven reduction of bromopalladate(II) is optimized to reproducibly obtain different Pd NS at the water/organic layer interface. In this soft interfacial strategy, a redox potential driven reaction has been performed, forming the thermodynamically more stable (>10 4 ‐fold) PdBr4 2− precursor from PdCl4 2− by adding extra metal bromides. In the process, the reductant, Hantzsch dihydropyridine ester (DHPE), is aromatized. Interestingly, alkali metal bromides devoid of coordination propensity exclusively evolve Pd nanowires (Pd NWs), whereas in the case of transition metal bromides the metal ions engage the 'N' donor of DHPE at the interface, making the redox reaction sluggish. Hence, controlled Pd nanoparticles growth is observed, which evolves Pd broccolis (Pd NBRs) and Pd nanorods (Pd NRs) at the interface in the presence of NiBr2 and CuBr2, respectively, in the aqueous solution. Thus, the effect of diverse metal bromides in the reaction mixture for tailor‐made growth of the various Pd NS is reported. Among the as‐synthesized materials, the Pd NWs stand to be superior catalysts and their efficiency is almost 6 and 2.5 times higher than commercial 20 % Pd/C in the electrooxidation of ethanol and Cr VI reduction reaction by formic acid, respectively. Abstract : Shape‐selective synthesis : Various intriguing nanostructures of palladium can be made by an aromaticity‐driven interfacial synthetic technique induced by bromide salts. The reduction of the palladium ions evolves depending upon the counter cations of the added bromide ions. The nanostructures exhibit outstanding catalytic activities towards electrooxidation of ethanol and chromium(VI) reduction by formic acid in comparison with commercial palladium carbon material.